2010
DOI: 10.1111/j.1582-4934.2009.00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and retention of HPV16 E7 to the endoplasmic reticulum enhances immune tumour protection

Abstract: The endoplasmic reticulum (ER) is where the major histocompatibility complex (MHC) class I molecules are loaded with epitopes to cause an immune cellular response. Most of the protein antigens are degraded in the cytoplasm to amino acids and few epitopes reach the ER. Antigen targeting of this organelle by Calreticulin (CRT) fusion avoids this degradation and enhances the immune response. We constructed a recombinant adenovirus to express the E7 antigen with an ER-targeting signal peptide (SP) plus an ER reten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…These results are consistent with previous studies showing that the linkage of E6 and E7 to ER chaperoning proteins causes the translocation of these proteins from the nucleus to the ER (14,26,27,29), resulting in an almost null signal in the nucleus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with previous studies showing that the linkage of E6 and E7 to ER chaperoning proteins causes the translocation of these proteins from the nucleus to the ER (14,26,27,29), resulting in an almost null signal in the nucleus.…”
Section: Discussionsupporting
confidence: 93%
“…In a previous study using mice, we demonstrated that treatment with an adenovirus (Ad SP-E7-KDEL) expressing antigen E7 fused to a CRT signal peptide (SP: MLLPVPLLLGLLGLAAAL) and a retention peptide (KDEL) exerted a protective antitumor effect equal to that obtained following treatment with the same antigen fused to CRT ( 14 ). In the present study, an improved vaccine was constructed that includes the E6 and E7 antigens, which provides a better antitumor effect according to the literature ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…These experiments nevertheless, were performed employing DNA vaccines to produce the chimeric antigen [14][15][16][17]. Using adenoviral vectors, we have demonstrated that the fusion of peptides commonly found in the endoplasmic reticulum (ER) (e.g., calreticulin) to an antigen, resulted in the retention of the antigen in the ER, improving its presentation to the MHC I [18]. These experiments indicate that enhanced antigen presentation to the MHC I results in a better cellular immune response [17][18][19].…”
Section: Antigen Modeling To Optimize Mhc Primingmentioning
confidence: 99%
“…Using adenoviral vectors, we have demonstrated that the fusion of peptides commonly found in the endoplasmic reticulum (ER) (e.g., calreticulin) to an antigen, resulted in the retention of the antigen in the ER, improving its presentation to the MHC I [18]. These experiments indicate that enhanced antigen presentation to the MHC I results in a better cellular immune response [17][18][19]. Taking in account these results, it is possible to use the same strategy and, for example, fusing calreticulin to antigens expressed by L. lactis in order to increase the immunogenicity.…”
Section: Antigen Modeling To Optimize Mhc Primingmentioning
confidence: 99%
See 1 more Smart Citation